2016
DOI: 10.1177/0895904816631099
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Coaching to Improve Teacher Practice Across Grades and Subjects: New Experimental Evidence

Abstract: This article analyzes a coaching model focused on classroom management skills and instructional practices across grade levels and subject areas. We describe the design and implementation of MATCH Teacher Coaching among an initial cohort of 59 teachers working in New Orleans charter schools. We evaluate the effect of the program on teachers' instructional practices using a block randomized trial and find that coached teachers scored 0.59 standard deviations higher on an index of effective teaching practices com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 45 publications
2
32
0
2
Order By: Relevance
“…One potential explanation is that longer, more intensive professional learning interventions may include a broader focus, while shorter interventions may include more narrowly targeted focal areas, producing larger effects in those targeted areas. For example, some researchers argue that teachers master complex forms of instruction when they first work on smaller routines and then build up to more complex activity (e.g., see Cai et al, 2017a, 2017b; Kraft & Blazar, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that longer, more intensive professional learning interventions may include a broader focus, while shorter interventions may include more narrowly targeted focal areas, producing larger effects in those targeted areas. For example, some researchers argue that teachers master complex forms of instruction when they first work on smaller routines and then build up to more complex activity (e.g., see Cai et al, 2017a, 2017b; Kraft & Blazar, 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 4 When multiple articles were published using the same set of data, we included articles when they reported results from different outcomes (Abry et al, 2013; Rimm-Kaufman et al, 2014), different cohorts (Blazar & Kraft, 2015; Kraft & Blazar, 2017), or different years (Matsumura et al, 2012, 2013) but chose only one of the studies when the samples, outcomes, and periods of measurement were overlapping (Vernon-Feagans et al, 2013, instead of Amendum, Vernon-Feagans, & Ginsberg, 2011). …”
mentioning
confidence: 99%
“…Research has identified a positive impact of learning in virtual worlds, especially when simultaneously engaging multiple users, attributed to increased engagement (Wrzesien and Alcañiz Raya, 2010[40]), the co-construction of knowledge (De Lucia et al, 2009[41]; Jamaludin, Chee and Ho, 2009 [42]), collaboration (Jarmon et al, 2009[43]), and the promotion of critical thinking (Herold, 2010[44]). Although mostly limited to English as a second language teaching, there are some case studies using an online platform, Second Life, for prospective teachers to gain teaching experience during their practicum (Cheong, 2010[45]; Kozlova and Priven, 2015 [46]).…”
Section: How To Adapt Initial Teacher Preparation To Remote and Hybrimentioning
confidence: 99%